The Shipwreck Yenikapı 7 from the Theodosian Harbour in Istanbul, Türkiye: A Preliminary Report - Özsait-Kocabaş, Işıl (The international journal of nautical archaeology, 2025)
During the Yenikapı salvage excavations carried out by the Istanbul Archaeological Museums in Türkiye, the shipwreck Yenikapı 7 was discovered in the Theodosian Harbour. Experts from Istanbul University’s Division of Conservation of Marine Archaeological Objects studied the hull of the shipwreck, which was dated to the 10th century AD based on its stratigraphic layer. The hull remains measured 6.6 m in length and 2.10 m in width, with all surviving timbers found in their original place. Yenikapı 7's hull exhibited unique features such as a flat-floored boxier hull at the cross-section amidships, bilge keels, rounded limber-holes, and a rockered keel. The planking of the shipwreck, which had a hull of mixed construction, is joined with edge dowels. This article presents the analysis of the shipwreck Yenikapı 7, including preliminary results, and comparative evaluations made with other similar Yenikapı shipwrecks.